2015
DOI: 10.1159/000438993
|View full text |Cite
|
Sign up to set email alerts
|

The Suppressive Effect of Quercetin on Toll-Like Receptor 7-Mediated Activation in Alveolar Macrophages

Abstract: Respiratory viral infections that cause chronic airway and lung disease can result in the activation of the innate immune response. Alveolar macrophages (AMs), one of the first lines of defense in the lung, are abundantly located in alveoli and the respiratory tract. Flavonoids found in fruits and vegetables exhibit cytoprotective effects on various cell types. In this study, we investigated the effect of quercetin on activation of AMs that had been exposed to imiquimod, a ligand of Toll-like receptor (TLR) 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…Liu, Xue, Li, Ao, & Lu, 2013), as well as LPS-induced lung injury (Huang, Zhong, & Wu, 2015). The beneficial effect of Quercetin involving TLR modulation was further established in a study on mouse alveolar macrophage cultures, where Quercetin attenuated TLR7-induced expression of TNF-α and IL-6 (Yasui, et al, 2015). Finally, in another study on LPS-stimulated human peripheral blood mononuclear cells (PBMCs), Quercetin was able to suppress the secretion of TNF-α, IL-1β, and IL-6 from PBMCs, and reduced the mRNA expression of TLR2 and NF-κB (M.…”
Section: Pharmacological Approaches Targeting Tlr/nf-κb and Oxidatmentioning
confidence: 99%
“…Liu, Xue, Li, Ao, & Lu, 2013), as well as LPS-induced lung injury (Huang, Zhong, & Wu, 2015). The beneficial effect of Quercetin involving TLR modulation was further established in a study on mouse alveolar macrophage cultures, where Quercetin attenuated TLR7-induced expression of TNF-α and IL-6 (Yasui, et al, 2015). Finally, in another study on LPS-stimulated human peripheral blood mononuclear cells (PBMCs), Quercetin was able to suppress the secretion of TNF-α, IL-1β, and IL-6 from PBMCs, and reduced the mRNA expression of TLR2 and NF-κB (M.…”
Section: Pharmacological Approaches Targeting Tlr/nf-κb and Oxidatmentioning
confidence: 99%
“…Earlier pharmacological studies have shown that flavonoids, chemical constituents of traditional Chinese medicine, have anti-inflammatory and analgesic effects. At the same time, they played anti-inflammatory effects through other pathways and regulation of inflammatory mediators such as IL-1β, IL-6, and TNF-α and their receptors ( Li et al, 2015 ; Yasui et al, 2015 ). In this study, most of the flavonoids were extracted by systematic solvent method.…”
Section: Introductionmentioning
confidence: 99%
“…Although quercetin has previously been reported to exert anti-inflammatory effects via modulation of Nrf2-signaling, these observations have mainly been made in models of acute lung injury or viral and bacterial infections (44) (45,46). Only a few studies have investigated the Nrf2-modulating effect of quercetin in relation to fibrosis, but these studies have focused on other organs including the heart (47) and liver (48).…”
Section: Discussionmentioning
confidence: 99%